Drug Interactions in Infectious Diseases - Piscitelli, Stephen C.; Rodvold, Keith; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2005)
Now extensively revised and significantly expanded, this second edition of the highly praised Drug Interactions in Infectious Diseases includes all the major recent advances in the understanding of drug interactions, with particular emphasis on the many new drugs approved since the first edition. The treatment of drug interaction mechanisms has increased to fill two chapters, allowing a more detailed description of absorption, metabolism, and excretion, as well as describing the growing knowledge of transport proteins. Recent reports of drug interactions, new case studies, and a new chapter outlining the regulatory perspective on interaction studies during drug development have been added. The chapter on study design and data analysis remains one of the best of its kind. The information contained in the book ranges from detailed tables of specific drug-drug interactions to in-depth discussions of interaction mechanisms and research issues. Comprehensive and up-to-date, Drug Interactions in Infectious Diseases, Second Edition concisely and authoritatively summarizes-for rapid access by all health care practitioners-the important drug interactions that occur during the treatment of infectious diseases, the mechanisms of their action, and the best strategies for their management in patient care.
to Drug Interactions -- Mechanisms of Drug Interactions I -- Mechanisms of Drug Interactions II -- Drug Interactions -- Drug Interactions With Antiretrovirals for HIV Infection -- Drugs for HIV-Related Opportunistic Infections -- Drugs for Tuberculosis -- Quinolones -- ?-Lactam Antibiotics -- Antifungal Agents -- Miscellaneous Antibiotics -- Drug-Food Interactions -- Drug-Cytokine Interactions -- Circumventing Drug Interactions -- Design and Data Analysis of Drug Interaction Studies.
Keywords: Infectious diseases; Pharmaceutical technology; Infectious Diseases; Pharmaceutical Sciences/Technology.